DYOTHELITISME DALAM KRISTOLOGI YOHANES CALVIN - Tonny Sutrisno; Billy Kristanto (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2019)
The continuity in the Orthodox understanding of the two wills of Christ, which is based on His two natures (Dyothelitism) is very important in order to understand about the Person of Christ, and how the work of redemption was perfectly performed by Him during His incarnation as the Logos that assumed a human nature. Dyothelitism which was represented by the thought of Maximus the Confessor is a reference in order to understand the Christology of two natures – one Person of Chalcedon, which has been accepted by the Church as an orthodoxy in the fight against Monothelitism and Monoenergism. The continuance between Maximus the Confessor’s Dyothelite thoughts and the thoughts and works of John Calvin in his Christology, is very important for the understanding of the implementation and perfect fulfillment of Christ's atoning work in the view of Reformed theology as represented by Calvin. KEY WORDS: Dyothelitisme; Monothelitisme; hypostasis; person; ousia; essence; nature; divinity; humanity